EXECUTION OF FIDUCIARY GUARANTEE ON THE MOTOR VEHICLE FINANCING AGREEMENT - Kifah Akifah (Indonesia Private Law Review, 2022)
Guarantee fiduciary this is basically for make it easy Public in get help credit, howeve iin implementation still arise various problem. Among them is in Thing execution guarantee fiduciary, where is the action arbitrary moment billing still bloom happen. Problem execution guarantee fiduciary return Becomes attention public post decision Court Constitution Number 2/PUU-XIX/2021 on August 31, 2021. There is an assumption that Decision Court Constitution the give convenience to company financing for execute guarantee fiduciary. Destination study this is (1) for analyze execution guarantee fiduciary in agreement financing vehicle motorized post Decision Court Constitution Number 2/PUU-XIX/2021, and (2) for analyze enforcement law to violations committed by debt collectors ( debt collectors ). Study this use method study law normative, with approach law. Fiduciary guarantee is basically conseptualized in order to deliver acess for public to gain credit. However in its implementation, it still arises various problem. Ome of the problem is its execuition. This problem become public attention after the decision made trough court contitutionale Number 21 PUU-X/X/X/2021 on August 2021. There is an assumtion that the decision of constitutional court to company financing for fiduciary guarantee. The purpose of this study is: first analyzing execution in fiduciary guarantee in agreement financing motorized vericle after the constitutional court decision Number 21 PUU-X/X/X/2021 was made. Second, this study also interded to analyze law enforcement to violations commited by debt collectors. This study use normative legal method consisting of legal approach.